Tinjauan Yuridis Tentang Larangan Pengajuan Praperadilan Oleh Orang Yang Berstatus Daftar Pencarian Orang (DPO) - Putri Rumondang Siagian; Syafruddin Kalo; Edi Yunara; Muhammad Hamdan (Iuris Studia: Jurnal Kajian Hukum, 2021)
This thesis is motivated by the principle of the rule of law which guarantees human rights to form the concept of pre-trial. Pre-trial in principle aims to carry out horizontal oversight of all acts of forced effort by law enforcers in the interests of criminal cases so that these actions do not conflict with legal and statutory regulations in addition to internal supervision within the apparatus itself. La Nyalla's pre-trial request as a suspect who fled or are in the status of a list of people search (DPO) status was learned that even though he was a DPO, La Nyalla won a pre-trial lawsuit which was stated through Court Decision Number: 19 / Pra.Per / 2016 / PN.Sby. After the pre-trial decision filed by the DPO suspect, the Supreme Court issued a Circular of the Supreme Court (SEMA) No. 1 of 2018 on March 23, 2018, discusses the prohibition on pre-trial submissions for suspects who have fled or are on the status of a search list (DPO). But the rules of SEMA No. 1 of 2018 seems to be deviated from the granting of pre-trial requests from suspects with DPO status through Court Decision Number 23 / Pid.Pra / 2018 / PN Pbr and Court Decision No.8 / Pid.Pra / 2018 / PN. Plw. Determination of DPO is a consequence of suspects who do not attend to the investigator's summons as stated in Article 112 paragraph (2) of the Criminal Procedure Code after proper calling is carried out in accordance with procedural rules. If viewed from Article 79 of the Criminal Procedure Code which regulates the submission of pre-trial, there is a limitation of the right of the suspect to file a pre-trial application for the suspect himself. The problem in this study is how are the pre-trial arrangements in the Criminal Procedure Code and the Criminal Procedure Code? how is the position of SEMA No. 1 of 2018 in legislation? How is the position of the suspect who is a DPO in filing a pre-trial application? This study uses theory. The method used in this study is a normative legal research and descriptive analytical. This study uses secondary data sources. This secondary data uses 3 (three) sources of data, namely primary legal material, secondary legal material, tertiary legal material. This data collection method is obtained from the library research. Data collection tool is done by studying documents. Analysis using the qualitative method then emphasizes the deductive method. The results of this study indicate that the KUHAP and RKUHAP through the commissioners' judges have given the suspect and the related parties the right to make horizontal supervision efforts on the actions of the investigator. SEMA is not authorized to prohibit citizens' rights. The position of SEMA No.1 Year 2018 is part of the legislation which is the nature of policy rules by binding to Supreme Court agencies as regulators Court Decision Number 23 / Pid.Pra / 2018 / PN Pbr and Decision No.8 / Pid.Pra / 2018 / PN. Plw became a breakthrough for pre-trial single judges in providing justice to suspects with DPO status for filing pre-trial